Acquisition target selection of a serial acquirer : case KONE Oyj - Rohrbach, Kira (My University, 2013)
Acquisitions are a way for a company to grow, enter new geographical areas, buy out competition or diversify. Acquisitions have recently grown in both size and value. Despite of this, only approximately 25 percent of acquisitions reach their targets and goals. Companies making serial acquisitions seem to be exceptionally successful and succeed in the majority of their acquisitions. The main research question this study aims to answer is: “What issues impact the selection of acquired companies from the point of view of a serial acquirer? The main research question is answered through three sub questions: “What is a buying process for a serial acquirer like?”, “What are the motives for a serial acquirer to buy companies?” and “What is the connection between company strategy and serial acquisitions?”. The case company KONE is a globally operating company which mainly produces and maintains elevators and escalators. Its headquarter is located in Helsinki, Finland. The company has a long history of making acquisitions and does 20- 30 acquisitions a year. By a key person interview, the acquisition process of the case company is compared with the literature about successful serial acquirers. The acquisition motives in this case are reflected upon three of the acquisition motive theories by Trautwein: efficiency theory, monopoly theory and valuation theory. The linkage between serial acquisitions and company strategy is studied through the key person interview. The main research findings are that the acquisition process of KONE is compatible with a successful acquisition process recognized in literature (RAID). This study confirms the efficiency theory as an acquisition motive and more closely the operational synergies. The monopoly theory can only vaguely be supported by this study, but cannot be totally rejected because of the structure of the industry. The valuation theory does not get any support in this study and can therefore be rejected. The linkage between company strategy and serial acquisitions is obvious and making acquisitions can be seen as growth strategy and a part of other company strategies.